The Study of Water Hammer Protection for Water Pipelines Containing Reversed Siphon Pipes With Special Large-Scale Dimensions - Hui Wang; Weibing Du; Xin Li; Xiaolei Zhang; Shuyu Liu; Yading Chen; Xiaoyi Guo (Geofluids)
The study focuses on a key component of the Yangtze–Huaihe River Diversion Project—the Qiliqiao to Xincheng water supply pipeline section, which includes a megascale inverted siphon structure. A one-dimensional mathematical model is developed to simulate water hammer phenomena in transmission pipelines containing the large siphon. A comparative analysis is conducted to evaluate the protective effects of linear and nonlinear valve closure strategies. The optimal valve closure scheme is explored by parameterizing the valve closing duration and buffering time. The impact of air valves installed near the inverted siphon during hydraulic transition processes is examined, and the transient variations of key hydraulic parameters during the entire valve closure operation are systematically characterized. Under long-term operational conditions with Manning’s coefficient degradation, the designed pipeline maintains a hydraulic head surplus of 7.34 m, fully meeting long-distance water supply requirements. Air valves effectively reduce the peak pressure magnitude by 80%. Under linear valve closure conditions, only the high-elevation air valves exhibit significant exhaust behavior. In contrast, nonlinear closure strategies reduce the minimum internal pressure of the pipeline and suppress vaporization, thereby reducing the air valve discharge volume. Finally, the study identifies an optimal time coordination scheme by adjusting the closure timing of individual pumps and the interval between adjacent pump shutdowns.